Proceedings of the 16th International Seminar on Paste and Thickened Tailings 2013
DOI: 10.36487/acg_rep/1363_35_pirouz
|View full text |Cite
|
Sign up to set email alerts
|

Flow through tilt flume testing for beach slope evaluation at Chuquicamata Mine Codelco, Chile

Abstract: A series of tilting (variable slope) flume tests were undertaken at the pilot plant facility at Chuquicamata copper mine in northern Chile to study the achievable tailings beach slope for different tailings solids concentrations and flowrates. The pilot plant facility was part of a prefeasibility study into upgrading the existing conventional tailings disposal facility, to a thickened tailings disposal scheme. The tilting flume facility was included into the pilot plant trial to produce reliable data for verif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The testing of each combination of equations involved validating the predicted launder slopes against some relevant data. The data used for validation was gathered in three separate flume trials by the author and his colleagues; The first two sets of data were gathered at the Peak gold mine and the Sunrise Dam gold mine (Fitton 2007), and the third set was gathered at the Chuquicamata copper mine (Pirouz et al 2013).…”
Section: Validating Datamentioning
confidence: 99%
“…The testing of each combination of equations involved validating the predicted launder slopes against some relevant data. The data used for validation was gathered in three separate flume trials by the author and his colleagues; The first two sets of data were gathered at the Peak gold mine and the Sunrise Dam gold mine (Fitton 2007), and the third set was gathered at the Chuquicamata copper mine (Pirouz et al 2013).…”
Section: Validating Datamentioning
confidence: 99%
“…It is noted that recent flow-through flume testing at the Chuquicamata mine (Pirouz et al, 2013) found that plug flow prevailed when the slurry exhibited a sufficiently high yield stress. This sets a new challenge for practitioners in designing storages for such thick tailings, requiring a new approach to such flow regimes.…”
Section: 7mentioning
confidence: 99%
“…Fitton (2007) carried out a numerical analysis of different width-to-depth (w/d) ratios for a limited number of such channels, and after comparing the predicted results against experimentally measured data, recommended 5.5:1. In this present study some effort has been made to back-calculate the width-to-depth ratio (w/d) for each of the self-formed channels that were observed in a series of flume experiments that were recently carried out at the Chuquicamata copper mine by ATC Williams (Pirouz et al, 2013).…”
Section: Channel Aspect Ratiomentioning
confidence: 99%